Essentials of psychology - Kassin, Saul M.; Privitera, Gregory J.; Clayton, Krisstal D., 1978- (Los Angeles Sage, 2023)
"Essentials of Psychology propels students into a clear, vibrant understanding of psychological science through concise explanations, real-life examples, and active practice. Introductory psychology may be a student's first exposure to the scientific method-or a step toward a career in the field. This book takes an integrative approach that meets individuals where they are and builds from there"--
Includes bibliographical references and index.
Keywords: Psychology